Development and Validation of a Reversed-Phase Chiral HPLC Method to Determine the Chiral Purity of Bulk Batches of (S)-Enantiomer in Afoxolaner. (22nd November 2019) - Padivitage, Nilusha; Kumar, Satish; Rustum, Abu
Abstract: Afoxolaner is a new antiparasitic molecule from the isoxazoline family that acts on insect acarine g-aminobutyric acid and glutamate receptors. Afoxolaner is a racemic mixture, which has a chiral center at the isoxazoline ring. A reversed-phase chiral HPLC method has been developed to determine the chiral purity of bulk batches of ( S )-enantiomer in afoxolaner for the first time. This method can also be used to verifythat afoxolaner is a racemic mixture, which was demonstrated by specific rotation. ChromSword, an artificial intelligence method development tool, was used for initial method development. The column selected for the final method was CHIRALPAK AD-RH (150 × 4.6 mm, 5 μm particle size), maintained at 45°C, and isocratic elution using water–isopropanol–acetonitrile (40 + 50 + 10, v/v/v) as the mobile phasewith a detection wavelength of 312 nm. The run time for the method was 11 min. The resolution and selectivity factors of the two enantiomers were 2.3 and 1.24, respectively. LOQ and LOD of the method were 1.6 and 0.8 μg/mL, respectively. This method was appropriately validated according to International Conference on Harmonization guidelines for its intended use.